PENERAPAN MODEL PERTUMBUHAN LOGISTIK DALAM MEMPROYEKSIKAN JUMLAH PENDUDUK DI KABUPATEN SUMENEP - Nadya Nurmadhani; Faisol Faisol (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2022)
Population projection is not a population forecast but a scientific calculation based on assumptions of the components of the population growth rate, namely births, deaths and migration. These three components determine the size of the population and the age structure of the population in the future. In order to determine the assumptions of future developmental levels of births, deaths and displacement, data are needed that describe trends from the past to the present. Here the author will determine the projected population growth in Sumenep Regency on Madura Island using a logistic growth model. The population census of Sumenep Regency was obtained from the BPS (Central Statistics Agency) of Sumenep Regency from 2010 to 2020. Based on the results of the study, it was obtained that the Craying capacity was 1,141,132.5. The author can conclude that the model that is closest to the actual census value is called the best model by looking for the MAPE value of each model to find out the census value that is closest to the true value and here the logistical model 9 is the most accurate compared to other models, with a value of  and produces the equation  and based on model 9, the writer looks for the population census in 2040 with the value of  resulted in 1,127,590.627 people.